Metal complexes of dipyridine hexaaza macrocycles. Structural differences between 18-and 20-membered macrocycles on complexation - Branco, L (2015)
The hexaaza macrocycles 3,6,14,17,23,24-hexaazatricyclo[ 17.3.1.1(8,12)]tetracosa-1(23), 8,10,12(24), 19,21-hexaene ([18]py(2)N(4)) and 3,7,15,19,25,26-hexaazatricyclo[19.3.1.1(9,13)]hexacosa-1(25), 9,11,13(26), 21,23-hexaene ([20]py(2)N(4)) were synthesised. The protonation constants of both compounds and the stability constants of their complexes with a wide range of metal ions (Mn2+, Ni2+, Cu2+, Zn2+, Cd2+, Pb2+, Mg2+, Ca2+, Ba2+, La3+ and Gd3+) were determined at 25degreesC with ionic strengths of 0.10 mol dm(-3) in KNO3. The overall basicity of [20] py(2)N(4) is 3.20 log units larger than that of [18]py(2)N(4) due to the weaker repulsion between the contiguous protonated ammonium sites, which are separated by propyl chains in [20]py(2)N(4) rather than ethyl chains in [18]py(2)N(4). The stability constants of complexes of each metal decrease as the cavity size of the macrocycle is increased, taking into account the difference in basicity of the ligands; the values for the Cu2+, Ni2+ and Zn2+ complexes of both ligands are exceptionally high. Single crystal structures of complexes [Ni([18]py(2)N(4))](ClO4)(2).2CH(3)CN (1), [Cu([18]py(2)N(4))](ClO4)(2).2CH(3)CN (2), [Co([20]py(2)N(4))]-[Co(H2O)(6)](0.5)(SO4)(2).CH3OH.4H(2)O (3), [Ni([20]py(2)N(4))](ClO4)(2)(4) and [Cu([20]py(2)N(4))](ClO4)(2) (5) were determined. In all complexes, the metal centre exhibit a hexaco-ordinate environment and the macrocycle adopts a twisted helical topology. The effect of the cage sizes of [18]py(2)N(4) and [20]py(2)N(4) on the molecular dimensions of metal complexes of both macrocycles is evaluated and a significant decrease in the helicity is observed in complexes of the 18-membered macrocycle compared to complexes of the 20-membered ring. The X-ray structural results, together with molecular mechanics calculations and NMR studies performed for metal complexes of both macrocycles, indicate that both ligands have enough flexibility to encapsulate smaller and larger metal ions, although it is clear that [20]py(2)N(4) is more flexible than [18]py(2)N(4).